Low-intensity ultrasound promotes uterine involution after cesarean section: the first multicenter, randomized, controlled clinical trial. (31st December 2022) - Qin, Yi; Zhao, Xiaobo; Dong, Xiaojing; Liu, Juntao; Wang, Longqiong; Wu, Xiaohua; Peng, Bin; Li, Chengzhi
Abstract: Objective: To evaluate the clinical efficacy and safety of low-intensity ultrasound (LIUS) in promoting uterine involution and relieving postpartum pain. Methods: The randomized controlled clinical trial in this study was conducted at five centers in three regions across China from June 2014 to December 2014. A total of 498 subjects were randomly divided into two groups. The LIUS group received ultrasound treatment, and the control group received sham ultrasound treatment. The fundal height and visual analogue scale (VAS) scores of the subjects following cesarean section were recorded separately before and after five treatments. The incidence of adverse events was recorded, while the records on lochia duration were obtained by telephone follow-up. The Full Analysis Set (FAS) comprised all subjects randomized who received at least one treatment. The Per-Protocol Set (PPS) comprised all patients who did not seriously violate the study protocol and had good compliance with complete report forms. Efficacy analyses were performed based on the FAS and PPS. All safety analyses were performed based on the safety set (SS), which included all patients who received at least one treatment. Results: In the analysis of PPS and FAS, the LIUS group performed better than the control group in reducing the fundal height, shortening the duration of lochia, and relieving postpartum pain, with a significant difference between the two groups ( p  < 0.0001). In the SS analysis, there were no treatment-related adverse events observed in either group. Conclusions: The LIUS therapy is safe and effective, which contributes to uterine involution and the alleviation of postpartum pain.